Investment in post-pandemic neglected social sectors by local governments of Moquegua in the period 2007-2023 - Flores-Arocutipa, Javier (2024)
The intention was to demonstrate that investments in the education and health sectors continue to be lower between 2021-2023. Little was learned from the COVID 19 pandemic. To do this, it was necessary to prove that the budget allocated to the transportation sector is greater than that allocated to education and health by local governments, between the years 2007-2023. The research instrument was the documentary analysis of 17 PIM and accrual files; ANOVA was used to show the statistical inference. Among the PIM results, the p value is less than 0.05, indicating that investment is greater in the transportation sector than in the education and health sectors. The results of the ANOVA test for accruals have a p value of less than 0.05, indicating that the differences in expenditure execution between these sectors are significant and that the transportation sector has a significantly higher accrued amount. Although the health crisis revealed the enormous health limitations, in education the investment policies remain the same in the region by local governments.